The Effect of Lavender Aromatherapy on Sleep Quality in Hemodialysis Patients - Dabirian, Azam; Sadeghim, Maryam; Mojab, Faraz; Talebi, Atefeh (Advances in Nursing & Midwifery, 2013)
Abstract: Background and Aim: Sleep is one of the biological rhythms and necessary for physical and mental health. More than of hemodialysis patients suffer from major sleep disturbances. Aromatherapy is one of the ways to improve sleep quality. The aim of this study was to determine effect of lavender aromatherapy on sleep quality in hemodialysis patients. Materials and Method: This research was quasi-experimental study, pre-post-intervention with one group on hemodialysis patients that were selected based on sampling method. A -part questionnaire including demographics and items related to the condition, Pittsburgh Sleep Quality Index questionnaire and was used for data collection, validated and made reliable by content and test-retest methods respectively. Intervention was included inhalation of drops of lavender essential oil dropped on a piece of cotton placed in a small box near patients˙ pillow, within - cm distance from the patient. Aromatherapy was performed for weeks including a day during the week before night sleep. The data analyzed using SPSS (version ) and statistical tests. Results: Results showed a significant deference was found between mean score of sleep quality before and after intervention (P< ) and a significant decrease (P< ) in each of the dimensions of sleep quality than the before time of lavender essential oil inhalation (P< ). Conclusion: The study revealed inhalation of lavender essential oil has a favorable effect on sleep quality in hemodialysis patients. Inhalation of lavender essential oil improves the dimensions of sleep quality, including subjective sleep quality, sleep latency, habitual sleep efficiency, sleep duration, sleep disturbances and daytime dysfunction in hemodialysis patients. Keywords: Sleep, Hemodialysis, Aromatherapy, Essential oil, lavender